2017
DOI: 10.1093/toxsci/kfx202
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium Exposure Impairs Cognition and Olfactory Memory in Male C57BL/6 Mice

Abstract: Cadmium (Cd) is a heavy metal of high interest to the superfund initiative. Recent epidemiology studies have suggested a possible association between Cd exposure and cognitive as well as olfactory impairments in humans. However, studies in animal models are needed to establish a direct causal relationship between Cd exposure and impairments in cognition and olfaction. This study aims to investigate the toxic effect of Cd on cognition and olfactory function in mice. One group of 8-week-old C57BL/6 male mice was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(42 citation statements)
references
References 82 publications
2
40
0
Order By: Relevance
“…We also found that Cd markedly reduced the expression of synaptic proteins (PSD-95, SNAP-23, and SYN) in the cortex and hippocampus of Cd-treated mice, and administration of caffeine significantly enhanced its expression. Furthermore, studies have reported that Cd is neurotoxic and exposure to Cd is responsible for impaired cognition and memory in several animal models [72,73]. We performed behavioral analysis (MWM and Y-Maze) to measure spatial learning and memory function.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that Cd markedly reduced the expression of synaptic proteins (PSD-95, SNAP-23, and SYN) in the cortex and hippocampus of Cd-treated mice, and administration of caffeine significantly enhanced its expression. Furthermore, studies have reported that Cd is neurotoxic and exposure to Cd is responsible for impaired cognition and memory in several animal models [72,73]. We performed behavioral analysis (MWM and Y-Maze) to measure spatial learning and memory function.…”
Section: Discussionmentioning
confidence: 99%
“…Cadmium can disturb the homeostasis of Cu and Zn ions in the brain of Cd-intoxicated animals (Wang and Du, 2013 ). It might also induce apoptosis of cerebral cortical neurons by altering Ca homeostasis and the Ca-mediated signalling pathway (Xu et al , 2011 ; Yuan et al , 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…A possible mechanism by which Cd induces these disorders may involve alteration of copper (Cu), zinc (Zn), iron (Fe), and calcium (Ca) homeostasis (Wang & Du, 2013 ). Chelation therapy is the most commonly used therapeutic strategy for the treatment of toxic metal poisonings (Flora & Pachauri, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies using animal models suggest that cadmium-induced changes in blood-brain barrier permeability and neuronal damage may be the result of cadmium-mediated generation of reactive oxygen species (ROS) [ [18] , [19] , [20] , [21] , [22] ]. This damage is associated with negative impacts on memory and cognitive behavior [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%